Model Pembelajaran Cooperative Learning Crossword Puzzle pada Mata Pelajaran Al-Qur’an Hadits - Muzakki, Ahmad; Aminuddin, Yusuf (Madrasah Ibtidaiyah Education Journal, 2023)
This article was written to review the Cooperative Learning Crossword Puzzle Learning Model which is implemented in the Al-Qur'an Hadith subject. The type of research used in this research is Literature Review. The aim of writing this article is to explain the cooperative learning crossword puzzle learning model in the Al-Qur'ân Hadīth subject so that changes occur in students' activity and grades. The learning model requires preparation and research design. In this development, the model that will be developed refers to the Sugiyono Research and Development development model which consists of several steps, namely 1) potential and problems; 2) data collection; 3) product design; 4) design validation; 5) design revision; 6) product trials; 7) product revision; 8) trial use; 9) product revision; and 10) mass production.